Interactivity that matters - Tronstad, Ragnhild (Teatervitenskapelige studier, 2025)
Skilfully applied, interactivity is an ingredient that may boost engagement and enhance the performance experience of a young audience. However, it can also lead to confusion, banalisation and even embarrassment. What are the parameters for interactivity to be experienced as meaningful, and when is it unproductive? In this article I shall address how conceptions of artistic quality are challenged by contemporary practices of interactivity and audience participation in theatre for young audiences. The question will be discussed in relation to three performing arts productions presented in The Cultural Schoolbag (TCS): one participatory theatre performance and two interactive digital productions. The latter two were developed as part of Kulturtanken – Arts for Young Audiences Norway’s 3-year development project in digital mediation, FoNT (Formidling og Ny Teknologi/Mediation and New Technology). Equipped with theories of games and play, I shall discuss how the three projects succeed in presenting the kids with opportunities for meaningful interaction. I conclude by pointing out some of the parameters that are vital in order to provide meaningful interaction in performing arts aimed at a young audience – interactions that matter.